Allied health students as service providers in Aboriginal and Torres Strait Islander early childhood education programs: Perceptions of parents and educators - Helen Sargison; Anne E Hill; Renae Anderson; Jodie Copley; Jodie Booth (Bond University, 2021)
Early childhood education programs contribute significantly to children's health and educational outcomes. Responsive service delivery approaches that support Aboriginal and Torres Strait Islander children and families to access allied health services in the early years are needed to reduce the health/education equity gap in Australia, particularly given the high prevalence of otitis media in this population. This study investigated perspectives of parents and early childhood educators regarding speech pathology and occupational therapy student-delivered services in Aboriginal and Torres Strait Islander early childhood settings. Thirteen early childhood educators and nine parents participated in focus groups or interviews following delivery of interprofessional services. Data were analysed using descriptive qualitative analysis. Findings suggest parents and early childhood educators perceived allied health student-delivered services to be effective, and enabled conceptualisation of a community-centred model for allied health service delivery in Aboriginal and Torres Strait Islander early childhood settings. This model supports communities to directly and collaboratively influence the provision of allied health services, and highlights approaches that involve relationship-building and respectful collaboration.